Effects of aromatherapy massage with bergamot essential oil on vital sign, flexibility, stress level and stress hormone in healthy adults: a pilot study - Sungkamanee, Sudarat; Ladawan, Suphannika; Maharan, Sinthuporn; Aumput, Patchareeya; Srithawong, Arunrat; Sriraksa, Napatr (Archives of Allied Health Sciences, 2022)
Aromatherapy with essential oils has been shown to relieve stress and alleviate symptoms of musculoskeletal diseases. However, physiological changes generated by aromatherapy massage with bergamot oil are still limited. The objective of this study was to determine the effect of aromatherapy massage with bergamot essential oil in healthy subjects. Thirty-one healthy subjects received a 14-minute aromatherapy massage with bergamot oil at the back region three times a week for four weeks. Blood pressure, heart rate, respiratory rate, skin temperature, stress level, back flexibility, cortisol levels, and aldosterone levels were measured at baseline and the end of a 4-week aromatherapy massage with bergamot oil. The result showed that all parameters mentioned above except skin temperature, back flexibility, and diastolic blood pressure were significantly decreased after the intervention. Skin temperature and back flexibility were significantly increased after the intervention with aromatherapy massage with bergamot oil. Diastolic blood pressure was decreased after the intervention but did not reach statistical significance. In conclusion, a 4-week course of aromatherapy massage with bergamot oil at the back region could improve physiological parameters including autonomic, stress, back flexibility, and hormonal parameters.